“Caracterización fitoquímica y actividad biológica de Oryctanthus Spicatus (Loranthaceae)” - Guerrero Aleaga, Norma Daniela (2014)
The chemical composition of the ethereal, alcoholic and aqueous extracts obtained by maceration of leaves of Oryctanthus spicatus in samples collected in the province of Morona Santiago was characterized by techniques such as: phytochemical screening, finding: oils and greases, alkaloids, triterpenes and steroids, catechins, reducing sugars, lactones and coumarins, saponins, polyphenols and tannins, quinones, flavonoids, and bitter principles, Uv-Vis spectrophotometry to determine total phenols and chromatography in thin layer to observe the chromatographic profile of secondary metabolites in fractions obtained from each extract. Evaluating the antimicrobial activity using the agar diffusion method (Kirby- Bauer) and the serial double dilution technique for determining the minimum inhibitory concentration (MIC) against certified strains of aeruginosa ATCC 27853, E. coli ATCC 9637, B. subtilis subes spizizenii ATCC 6633, S. aureus ATCC 6538 and Candida albicans ATCC 10231 showing wide spectrum of the antibacterial activity but to a lesser extent compared to the standards.